UNCOVERING DERMATILLOMANIA: A REVIEW OF SKIN PICKING DISORDER - Łukasz Nosek; Agata Mytych; Marta Dziedziak; Julia Groszewska; Michał Romaniuk; Agata Rapior; Daria Julia Makowska-Woszczyk; Kinga Lubomska; Patrycja Jagura; Jan Romaniuk (International Journal of Innovative Technologies in Social Science, 2025)
Background: Excoriation disorder (dermatillomania) is a body-focused repetitive behavior characterized by recurrent skin picking that leads to tissue injury, emotional distress, and impaired functioning. Although formally classified in ICD-11 and DSM-5, the disorder remains underrecognized in clinical settings and often co-occurs with other psychiatric conditions. This review summarizes current evidence on the epidemiology, clinical profile, comorbidity patterns, and available treatment strategies, underscoring its clinical burden and therapeutic relevance.Methods: A narrative review of peer-reviewed clinical studies, epidemiological analyses, neurobiological investigations, and treatment trials was conducted, focusing on prevalence, risk factors, clinical outcomes, and therapeutic interventions for excoriation disorder.Results: The disorder affects approximately 3–4% of the population, predominantly females, with onset most often during adolescence and a chronic, relapsing course. Commonly affected areas include the face, arms, and hands, with episodes frequently preceded by anxiety or tension and followed by temporary relief. High rates of comorbidity, particularly with depression, anxiety, OCD, and body dysmorphic disorder, contribute to psychosocial disability, reduced quality of life, and an elevated risk of suicidal ideation. Clinical studies support behavioral therapies, especially cognitive-behavioral approaches such as habit reversal training, as first-line treatment. Pharmacological options, including serotonergic, opioid, or glutamatergic agents, as well as lamotrigine, show benefit in selected cases, although response rates remain variable.Conclusions: Excoriation disorder is a prevalent and burdensome condition with substantial psychiatric overlap and functional consequences. Early detection and integrated treatment combining behavioral interventions with targeted pharmacotherapy when appropriate are essential to improving outcomes and reducing long-term morbidity.